Degradation of Balinese Kitchen Utensil Lexicon: An Ecolinguistics Perspective - A.A. Pt. Suari; Ni Ketut Sri Rahayuni (Politeknik Negeri Bali, 2026)
This study examined the degradation of the Balinese kitchen utensil lexiconby analyzing its use across spatial and temporal dimensions in urban Denpasar. Datawere collected through documentation and a structured questionnaire administered torespondents selected using a multi-stage clustered sampling technique, with Denpasaridentified as the primary research cluster. Participants were grouped by age intoadolescents (12–25 years), adults (26–45 years), and elderly individuals (46–65 years).The analysis adopted an ecolinguistics framework that interpreted linguistic changethrough three key parameters: environment, diversity, and interaction, interrelation, andinterdependence. A mixed qualitative–quantitative approach was employed to examinepatterns of lexical recognition and use across generations. The findings revealed thatthe lexicon of Balinese kitchen utensils was largely retained among elderly respondents,who demonstrated high levels of familiarity and practical experience. In contrast,adolescents exhibited significant lexical degradation, as most were unfamiliar with theterms and had not actively used them in everyday practice. This generational disparityindicated an ongoing domain-specific language shift, driven by changes in domesticpractices and material environments in urban Balinese households.